(untitled) (A Luz em Cena: Revista de Pedagogias e Poéticas Cenográficas, 2024)
Taking lighting design as the object of this work, we will discuss how this practice can be combined with a more human future, when lighting is understood as one of the control mechanisms of the current economic system, capitalism, in contemporary times. This question arises with the advancement of 24/7 architectures in cities that do not sleep and aims to criticize the way of producing an architecture that is solely in favor of the production system and goes against circadian and social rhythms. The methodology developed for this work was a combination of bibliographic review and case studies, from which we can outline strategies to align lighting design with the interests and needs of human beings, also questioning the importance of experiencing scenic lighting for the construction of better everyday spaces.